2008
DOI: 10.3325/cmj.2008.3.364
|View full text |Cite
|
Sign up to set email alerts
|

Relation Between Burnout Syndrome and Job Satisfaction Among Mental Health Workers

Abstract: Mental health workers exhibited a moderate degree of burnout syndrome, but there were no significant differences regarding their occupation. Generally, both dimensions of job satisfaction and manifestations of occupational stress proved to be relevant predictors of burnout syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
1
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 35 publications
5
61
1
9
Order By: Relevance
“…Francuski istraživači izvješćuju da 26 % ženskog osoblja u bolnicama ima povećani rizik od oboljenja od psihičkih poremećaja. Štoviše, 32 % sudionica izvještava o umoru, 31 % o poremećajima spavanja, 28 % o zlouporabi droge te 21 % sudionica priznaje da ima psihijatrijsku dijagnozu, najčešće depresiju Osim toga, velik je problem među pomagačkim profesijama, pa tako i u sestrinstvu 2,4,5,6 , sindrom sagorijevanja na poslu (engl. burnout).…”
Section: Uvodunclassified
See 1 more Smart Citation
“…Francuski istraživači izvješćuju da 26 % ženskog osoblja u bolnicama ima povećani rizik od oboljenja od psihičkih poremećaja. Štoviše, 32 % sudionica izvještava o umoru, 31 % o poremećajima spavanja, 28 % o zlouporabi droge te 21 % sudionica priznaje da ima psihijatrijsku dijagnozu, najčešće depresiju Osim toga, velik je problem među pomagačkim profesijama, pa tako i u sestrinstvu 2,4,5,6 , sindrom sagorijevanja na poslu (engl. burnout).…”
Section: Uvodunclassified
“…Deskriptivni podaci prikazani su u tablici 1. Prosječna je dob sudionika 35,66 (raspon od 23 do 62 godine), a prosječne godine radnog U skladu s time, različita dosadašnja istraživanja pokazuju da su medicinske sestre zaposlene na psihijatrijskim odjelima općenito u velikom riziku od sagorijevanja 6,14,16,17,18,19,20,21 u usporedbi s medicinskim sestrama zaposlenima na drugim bolničkim odjelima te imaju više sagorijevanja na poslu 11,22,23 .…”
Section: Sudioniciunclassified
“…Job satisfaction have been reported to be positively correlated with good citizenship behaviours (Bateman & Organ, 1983), organizational commitment (Philips, 1994), pay satisfaction (Bolarin, 1993), task clarity and career commitment (Adeyemo & Aremu, 1999), personal self-efficacy beliefs (Buluç, & Demir, 2015), job performance (Büyükgöze, & Özdemir, 2017;Chamundeswari, 2013 (Schneider, 2003), positive affectivity (Agho, Price, & Mueller, 1992), leader-member exchange (Özdemir, & Büyükgöze, 2015), and work motivation (Tella, Ayeni, & Popoola, 2007). However, lower levels of employee satisfaction have been found to correlate with intention to leave (Coomber, & Barriball, 2007), job stress (Bemana, Moradi, Ghasemi, Taghavi, & Ghayoor, 2013), anxiety (Ferguson, Frost, & Hall, 2012), retention (Myers-Giacometti, 2005), and burnout syndrome (Ogresta, Rusac, & Zorec, 2008).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Gregov, Kovačevic´ and Sliškovic´ [7] determined that emergency physicians experienced significantly more intense and more frequent uncontrollable working situations, conflict between work and family roles, and unfavourable relationships with co-workers than physicians working in health centres. Ogresta, Rusac and Zorec [8] found that satisfactory wages and rewards, work climate, advancement opportunities, degree of rIgInAl ArtIcles And reVIews psychological and physical manifestation of occupational stress were significant predictors of emotional exhaustion. Job dissatisfaction, reduced self-efficacy, and low levels of workplace peer support in particular can lead to higher levels of cynicism [9].…”
Section: Introductionmentioning
confidence: 99%